2005
DOI: 10.1093/carcin/bgi229
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on multiple tumorigenic cascades involved in prostatic cancer progression and targeting therapies

Abstract: Recent advances on differently-expressed gene products and their functions during the progression from localized androgen-dependent states into androgen-independent and metastatic forms of prostate cancer are reported. The expression levels of numerous oncogenes and tumor suppressor genes in distinct prostatic cancer epithelial cell lines and tissues relative to normal prostate cells are described. This is carried out to identify the signaling elements that are altered during the initiation, progression and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
203
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(206 citation statements)
references
References 217 publications
(400 reference statements)
2
203
0
1
Order By: Relevance
“…Enhanced expression of EGFR/ErbB1 had been proven to correlate with high grades of prostate cancer malignancies and contribute to the progression from localized and AD prostate cancer to more metastatic and AI state (34,35), and the phosphorylation level of AKT which was the downstream gene of EGFR had been proven to correlate with androgen receptor level and promote castration-resistant cell growth (25). Importantly, AR was observed to be slightly downregulated in C4-2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of EGFR/ErbB1 had been proven to correlate with high grades of prostate cancer malignancies and contribute to the progression from localized and AD prostate cancer to more metastatic and AI state (34,35), and the phosphorylation level of AKT which was the downstream gene of EGFR had been proven to correlate with androgen receptor level and promote castration-resistant cell growth (25). Importantly, AR was observed to be slightly downregulated in C4-2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism, causing increased Tiam1 expression in HG-PIN lesions and prostate cancer, has yet to be determined, there are indications that it might result at least in part from increased Wnt/b-catenin signaling. The Wnt/b-catenin signaling pathway plays a central role in colon cancer development (for review see Oving and Clevers (2002)), but in several studies aberrant activation of Wnt/b-catenin signaling has also been implicated in the formation of PIN-like proliferative lesions as well as in prostate cancer progression (for review see Mimeault and Batra (2006); Yardy and Brewster (2005)). Interestingly, we recently identified Tiam1 as a Wnt-responsive gene that is upregulated in intestinal and colon tumours, and by comparing tumour development in APC mutant multiple intestinal neoplasia (Min) mice expressing or lacking Tiam1, we found that Tiam1 deficiency significantly reduces the formation and growth of intestinal polyps in vivo (Malliri et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signalling might be one of the most critical signalling mechanisms for cancer cells, including prostate cancer cells [1,3,10]. To investigate the effects of EGFR on PC3 cells, we analysed signalling molecules Figure 2.…”
Section: Exogenous Expression Of P27 Inhibits Egfr/pi3k/ Akt Signallimentioning
confidence: 99%